2018
DOI: 10.1097/01.jaa.0000544305.38577.84
|View full text |Cite
|
Sign up to set email alerts
|

Burnout, job satisfaction, and stress levels of PAs

Abstract: Overall, PAs rate aspects of work life favorably. Further research on factors that contribute to the PA work experience may help inform interventions aimed at improving job satisfaction among healthcare professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 19 publications
1
41
1
1
Order By: Relevance
“…Additionally, we did not discuss any interdisciplinary differences in PCC experiences. Although our analysis did not detect any differences between survey responses left by advanced practice providers vs. their physician counterparts, interdisciplinary differences in PCC experiences do exist 14,[80][81][82] and warrant closer study. It is also possible that the study underemphasized differences between PCCs at different VHA sites and overlooked some of the issues faced by non-VHA clinicians that are not salient in the VHA context.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Additionally, we did not discuss any interdisciplinary differences in PCC experiences. Although our analysis did not detect any differences between survey responses left by advanced practice providers vs. their physician counterparts, interdisciplinary differences in PCC experiences do exist 14,[80][81][82] and warrant closer study. It is also possible that the study underemphasized differences between PCCs at different VHA sites and overlooked some of the issues faced by non-VHA clinicians that are not salient in the VHA context.…”
Section: Discussioncontrasting
confidence: 67%
“…5,6 Research suggests that clinician well-being is negatively affected by organizational factors, such as excessive workload, insufficient control over work processes, heavy clerical burdens, misalignment with leadership's values, inadequate support and resources, and lack of collaborative working relationships. [7][8][9][10][11][12][13][14][15][16] However, as a recent literature review highlights, the effect of organizational factors associated with different types of practice environments is poorly understood. 10 Clinician well-being in integrated health systems (or integrated delivery systems) is especially relevant given the accelerating trend toward practice consolidation and integration.…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies indicate that job and career satisfaction remain high [11,36]. The adaptable nature of the PA role lends itself to specialty transition, which may serve as a buff er against the long-term eff ects of burnout [34]. However, the profession lacks rigorous, longitudinal, and robust studies on factors that contribute to burnout.…”
Section: Resultsmentioning
confidence: 99%
“…The literature focused on PA burnout is primarily limited to rural and specialty settings. However, one national survey that assessed work-life experiences-including burnout, happiness, and work-related stress-consisted of responses from 7,857 PAs from multiple specialties and locations [34]. Results of this national survey revealed that 21.4 percent of PAs felt some degree of cynicism, and 10.4 percent reported experiencing a low sense of personal accomplishment.…”
Section: Burnoutmentioning
confidence: 99%
See 1 more Smart Citation